RETRACTED: Bruton's Tyrosine Kinase Inhibition Attenuates the Cardiac Dysfunction Caused by Cecal Ligation and Puncture in Mice - O'Riordan, Caroline E.; Purvis, Gareth S. D.; Collotta, Debora; Chiazza, Fausto; Wissuwa, Bianka; Al Zoubi, Sura; Stiehler, Lara; Martin, Lukas; Coldewey, Sina M.; Collino, Massimo; Thiemermann, Christoph (Frontiers in Immunology, 2019)
Sepsis is one of the most prevalent diseases in the world. The development of cardiac dysfunction in sepsis results in an increase of mortality. It is known that Bruton’s tyrosine kinase (BTK) plays a role in toll-like receptor signaling and NLRP3 inflammasome activation, two key components in the pathophysiology of sepsis and sepsis-associated cardiac dysfunction. In this study we investigated whether pharmacological inhibition of BTK (ibrutinib 30 mg/kg and acalabrutinib 3 mg/kg) attenuates sepsis associated cardiac dysfunction in mice. 10-week old male C57BL/6 mice underwent CLP or sham surgery. One hour after surgery mice received either vehicle (5% DMSO + 30% cyclodextrin i.v.), ibrutinib (30 mg/kg i.v.) or acalabrutinib (3 mg/kg i.v.). Mice also received antibiotics and an analgesic at 6 and 18 hours. After 24 hours, cardiac function was assessed by echocardiography in vivo. Cardiac tissue underwent western blot analysis to determine the activation of BTK, NLRP3 inflammasome and NF-κB pathway. Serum analysis of 33 cytokines was conducted by a multiplex assay. When compared to sham-operated animals, mice subjected to CLP demonstrated a significant reduction in ejection fraction (EF), fractional shortening (FS) and fractional area change (FAC). The cardiac tissue from CLP mice showed significant increases of BTK, NF-B, and NLRP3 inflammasome activation. CLP animals resulted in a significant increase of serum cytokines and chemokines (TNF-α, IL-6, IFN-, KC, eotaxin-1, eotaxin-2, IL-10, IL-4, CXCL10 and CXCL11. Delayed administration of ibrutinib and acalabrutinib attenuated the decline of EF, FS and FAC caused by CLP and also reduced the activation of BTK, NF-B and NLRP3 inflammasome. Both ibrutinib and acalabrutinib significantly suppressed the release of cytokines and chemokines. Our study revealed that delayed intravenous administration of ibrutinib and acalabrutinib attenuated the cardiac dysfunction associated with sepsis by inhibiting BTK, reducing NF-κB activation and the activation of the inflammasome. Cytokines associated with sepsis were significantly reduced by both BTK inhibitors. Acalabrutinib is found to be more potent than ibrutinib and could potentially prove to be a novel therapeutic in sepsis. Thus, the FDA-approved BTK inhibitors ibrutinib and acalabrutinib may be repurposed for the use in sepsis.